2018
DOI: 10.1007/s13258-018-0731-z
|View full text |Cite
|
Sign up to set email alerts
|

Locating QTLs controlling overwintering seedling rate in perennial glutinous rice 89-1 (Oryza sativa L.)

Abstract: A new cold tolerant germplasm resource named glutinous rice 89-1 (Gr89-1, Oryza sativa L.) can overwinter using axillary buds, with these buds being ratooned the following year. The overwintering seedling rate (OSR) is an important factor for evaluating cold tolerance. Many quantitative trait loci (QTLs) controlling cold tolerance at different growth stages in rice have been identified, with some of these QTLs being successfully cloned. However, no QTLs conferring to the OSR trait have been located in the pere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Glutinous rice 89-1 (Gr89-1) has overwintering ability and germinates through axillary buds during the following spring. Yields are the same as in a normal season (up to 6.29 t/hm 2 ) in Chongqing, China (Deng et al 2018). Other studies have revealed similar overwintering ability of Oryza longistaminata and Dongxiang wild rice (O. rufipogon) in south and southwest China (He et al 1996;Liang et al 2017;Mao et al 2015;Zhang et al 2017a, b).…”
Section: Introductionmentioning
confidence: 61%
“…Glutinous rice 89-1 (Gr89-1) has overwintering ability and germinates through axillary buds during the following spring. Yields are the same as in a normal season (up to 6.29 t/hm 2 ) in Chongqing, China (Deng et al 2018). Other studies have revealed similar overwintering ability of Oryza longistaminata and Dongxiang wild rice (O. rufipogon) in south and southwest China (He et al 1996;Liang et al 2017;Mao et al 2015;Zhang et al 2017a, b).…”
Section: Introductionmentioning
confidence: 61%
“…In previous studies, QTLs for overwinter germination rate (qPOG‐2, qPOG‐3, and qPOG‐7; Zhao et al, 2012) and overwinter emergence rate (qOSR2, qOSR3, and qOSR8; Deng et al, 2018) were localized in Gr 89‐1. In this study, all genes within the QTL loci were matched with NCBI and RAP‐DB databases to obtain 398 annotated genes.…”
Section: Resultsmentioning
confidence: 91%
“…Cultivar rice "Glutinous rice 89-1" (Gr 89-1) is an exceptional overwintering cold-tolerant germplasm resource originating from Chongqing, China (Zhao et al, 2007), whose axillary buds can withstand low temperatures at different altitudes and germinate the following year. Genetic studies have been conducted on the cold tolerance traits of Gr 89-1, including QTL localization of ratooning germinability (PRG), overwintering germinability (POG; Zhao et al, 2012), overwintering seedling rate (OSR; Deng et al, 2018), and global analysis of 3-leaf stage seedlings of Gr 89-1 exposed to a cold treatment (Pan et al, 2016). Here, RNA-seq was performed using another common indica cultivar rice, "R07," as cold intolerant comparator to explore the phenotype, physiology, transcriptome network, and cold tolerance mechanism of Gr 89-1.…”
Section: Introductionmentioning
confidence: 99%
“…Glutinous rice 89-1 is an overwintering rice variety, as its axillary buds are dormant during the winter and can germinate and regenerate the following spring. The yield of overwintering regeneration season is equivalent to that of current season (Deng et al, 2018;Chen et al, 2021). After cleaning and disinfection, 100 rice seeds were selected and placed in the germination box (10 rows × 10 columns), which was transferred to a light incubator under the conditions of 16 h light/8 h dark, 30 °C, and 70% humidity for 10 d. Seedlings were cultivated for three-and one-heart periods, and seedlings with consistent growth were used for the next treatment.…”
Section: Rice Materialsmentioning
confidence: 99%